Gambaran Body Image dan Status Gizi pada Remaja di SMAN 2 Kota Jambi - Wati, Widia; Indrawati, Iin; Ariyanto, Ariyanto; Chandra, Filius (3031-8572, 2024)
Adolescent nutritional status can be influenced by various factors, one of which is body image. Body image is a person's attitude about feeling satisfied or dissatisfied with his body, resulting in a negative or positive assessment of himself. Body image can occur due to the perception of a person or adolescent who tends to judge his body size larger than the actual size. the actions taken by adolescents often cause harm to themselves such as actions in losing weight by means of unhealthy diets and reducing the portion of food excessively so that it will affect their nutritional status. Based on the results of Riskesdas 2023, it shows that the prevalence of nutritional status of adolescents in Indonesia aged 16-18 years is 1.4% very thin, 6.7% thin, 78.3% normal 9.5% fat and 4.0% obese. This study aims to see the description of body image and nutritional status in adolescents at SMAN 2 Jambi City. This study uses descriptive research methods, the total population in this study was 36 students in class XI, the sample in this study amounted to 36 students, the sampling technique used total sampling. Body image perception was measured using the BSQ questionnaire while nutritional status was measured using digital scales and microtoise which was then calculated using the IMT / U formula. Data analysis was carried out univariately to present the characteristics of body image variables and nutritional status, the results of univariate analysis obtained that most adolescent girls had a 69.4% positive body image and most of 75% had normal nutritional status.